Transregional and Regional Elites - Connecting the Early Islamic Empire. - Hagemann, Hannah-Lena. (Studies in the History and Culture of the Middle East Series, 2020)
Studies in the History and Culture of the Middle East are published as supplement to Der Islam which was founded in 1910 by Carl Heinrich Becker, an early practitioner of the modern study of Islam. The mission of the series is the study of past societies of the Middle East, their belief systems, and their underlying social and economic relations--in their aim to cover the entire spectrum of the historically oriented humanities and social sciences.